Hydrogen as transportation fuel - Danish & Scandinavian Activities - Sloth, Mikael (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
The need for a replacement of fossil fuels is of increasing importance. Onwards 2030 the world population will increase by 24% and the number of cars worldwide will increase by 50%. To supply this increase in energy consumption will take an increase of 66% in global oil production. Such an increase is challenging given the fact that oil production is in decline in 33 of the 48 largest oil producing countries, and for every barrel of oil found the world consumes two barrels. Hydrogen is internationally recognized as a long term solution for replacing gasoline and diesel in the transportation sector and a solution for balancing increasing future renewable energy input in the energy system. Even though hydrogen as transportation fuel is a long term solution the early demonstration and commercial introduction of hydrogen and fuel cell cars in the transportation sector will happen during the coming decade. Recent indication from fuel cell manufacturers and the car industry suggest that